Preface - Supera-Markowska, Maria (Journal of Finance and Financial Law, 2022)
The purpose of this paper which serves as an introduction to the special edition of the quarterly of “Finanse i Prawo finansowe. Journal of Finance and Financial Law” under the title of Current Challenges for National Tax Policies and International Tax Coordination – Selected Issues from the Polish, Spanish and International Perspectives, is to outline major issues and challenges in shaping national and international tax policies. The research hypothesis is that, to a large extent, the economic consequences of the COVID-19 pandemic, but also the changing economic reality associated with the progressive internationalization and digitalization of business activity, pose numerous and significant challenges in the field of shaping tax policies, both at the national and international level. The research was carried out using a dogmatic-legal and legal-comparative method, taking into account the provisions of law, the body of literature as well as some economic data. The result of the research is to establish a starting point for further analysis of selected topics that reflect the major current challenges for national tax policies and international tax coordination. They include the question of legitimacy of taxes, the issues of correct realisation of the fiscal function of taxes while at the same time implementing the basic tax principles, the matter of tax compliance and the question of tax policy-shaping within the framework of the democratic law-governed state. Those issues presented from the Polish and Spanish perspectives, hopefully may provide an interesting contribution and make a valuable input to further discussions on the issue of shaping tax policies, both at the national and international levels.